INTERNAL COMPANY BEHAVIORAL FACTORS THAT INFLUENCE FINANCIAL FRAUD - SITUMORANG, FRENKY; Pane, Yonson (Journal Accounting International Mount Hope, 2024)
The aim to be achieved in this research is to obtain empirical evidence regarding the influence of profitability, capital turnover, financial leverage, asset structure, company size, influence on the Financial Fraud, The type of research that will be carried out is a type of quantitative research, namely research that obtains data in the form of numbers or qualitative data that is used. Companies that have complete data that can be used to analyze profitability, capital turnover, financial leverage, asset structure and company size. Return on Assets has no significant effect on the Financial Fraud, Capital Turnover has no significant effect on the Financial Fraud, Financial Leverage has a significant effect on the Financial Fraud, asset structure has no significant effect on the Financial Fraud, Company size has no significant effect on the Financial Fraud, (DTA Return on Assets, Capital Turnover, Financial Leverage, asset structure, Company Size) on the dependent variable (Financial Fraud) that can be produced by this equation is 32.7%, while the remaining 67.3% is influenced by other factors which are not included in this regression. This research only examines internal company finances with a focus on manufacturing companies only. It is hoped that this research can be used as consideration and reference material so that when investing, stakeholders choose transparent companies with a good level of supervision over the financial reporting process, so as to avoid fraudulent financial reporting.